Imaging of Pregnant and Lactating Patients: Part 1, Evidence-Based Review and Recommendations - Wang, Page I.; Chong, Suzanne T.; Kielar, Ania Z.; Kelly, Aine M.; Knoepp, Ursula D.; Mazza, Michael B.; Goodsitt, Mitchell M. (American journal of roentgenology (1976), 2012)
The objectives of this article are to discuss the current evidence-based recommendations regarding radiation dose concerns, the use of iodinated and gadolinium-based contrast agents, and the comparative advantages of multimodality imaging (ultrasound, CT, and MRI) during pregnancy and lactation. We also discuss the use of imaging to evaluate pregnant trauma patients. Maternal and fetal radiation exposure and dose are affected by gestational age, anatomic site, modality, and technique. The use of iodinated and gadolinium-based contrast agents during pregnancy and lactation has not been well studied in human subjects. Imaging should be used to evaluate pregnant trauma patients only when the benefits outweigh the risks.